2015
DOI: 10.1088/0964-1726/24/3/035016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidant on the performance of conductive polymer films prepared by vacuum vapor phase polymerization for smart window applications

Abstract: Conductive polymers synthesized by vacuum vapour phase polymerization (VPP) were investigated and optimized by changing the oxidant solution and VPP chamber parameters for their incorporation into ‘smart window’ electrochromic devices. Additionally, the interaction of two oxidant solutions with typical electrode materials (aluminium and indium tin oxide) were examined with respect to material etching, device cosmetics and long term device degradation (over 10 000 switch cycles). Devices made with conducting po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…With respect to power consumption, we also note that PEDOT:Tos typically has a good optical memory, in the sense that it can remain in a switched state also after disconnecting the power supply. 16 This allows for a lower total power consumption compared to inorganic-based systems that require continuous power to maintain their states. 12,41 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to power consumption, we also note that PEDOT:Tos typically has a good optical memory, in the sense that it can remain in a switched state also after disconnecting the power supply. 16 This allows for a lower total power consumption compared to inorganic-based systems that require continuous power to maintain their states. 12,41 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 PEDOT exhibits a high optical density blue color in its reduced state and a low optical density transparent blue color in its oxidized state. This makes it an excellent candidate for electrochromic applications in the visible wavelength region, such as smart windows 16,17 for buildings and the automotive industry. 17,18 Comparatively, electrochromism of PEDOT in the IR wavelength range has been only sparsely reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate report investigated the effect of various organic solvent additions to the Fe(Tos) 3 oxidant solution, but none outperformed the ethanol solution. 33 Alcohol based solvents have been used extensively in the VPP of EDOT 3,4,34,35 and several of them were trialled for the best electrical and optical properties of PEDOT. Similar to the studies on PEDOT:Tos, we show that ethanol provides the highest electrical conductivity for PEDOT:Tof before (3250 AE 122 S cm À1 ) and aer acid treatment (4430 AE 168 S cm À1 ) (Fig.…”
Section: Synthesis Of Highly Conductive Pedotmentioning
confidence: 99%
“…Hee et al [7] concluded that electrochromic windows are more suitable for applications in residential areas in cold climate regions. Brooke et al [8] investigated the effect of oxidant on the performance of conductive polymer films. They concluded that the oxidant Fe(Tos) 3 produced superior device performance with respect to optical switching, switch speed and optical relaxation.…”
Section: Introductionmentioning
confidence: 99%